2023
DOI: 10.3389/fdgth.2022.1023592
|View full text |Cite
|
Sign up to set email alerts
|

User engagement in mobile apps for people with schizophrenia: A scoping review

Abstract: Over the past decade, there has been an increase in the number of mobile apps designed for mental health proposes and mHealth has been perceived as a promising approach to help people with schizophrenia to manage their condition. However, adoption rates are relatively low and long-term user engagement is a major issue. The aim of this study is to identify and better understand what strategies and factors may influence user engagement and facilitate prolonged use of apps for people with schizophrenia to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Participants rated the MedActive to be highly acceptable and practical, and they expressed positive feedback and satisfaction with their experience using the app. This is in line with a recent review conducted on 28 studies by Simões de Almeida and Marques (2023) , which conclude that mobile app effectively enhances adherence to medication among patients with mental illnesses. This suggests that mobile apps may be an effective strategy to tackle many of the issues of chronic mental illnesses.…”
Section: Discussionsupporting
confidence: 92%
“…Participants rated the MedActive to be highly acceptable and practical, and they expressed positive feedback and satisfaction with their experience using the app. This is in line with a recent review conducted on 28 studies by Simões de Almeida and Marques (2023) , which conclude that mobile app effectively enhances adherence to medication among patients with mental illnesses. This suggests that mobile apps may be an effective strategy to tackle many of the issues of chronic mental illnesses.…”
Section: Discussionsupporting
confidence: 92%
“…There remains uncertainty about an appropriate 'dose' of engagement in digital mental health interventions [41] and the amount of time spent with a digital tool varies between different types of interventions, people or environments [42]. In the field of digital mental health therapies, the ideal "dose" of engagement varies depending on the environment, the individual using the therapy, and the type of intervention, because low participation may be a positive indicator if it indicates that users have already met their recovery objectives or are using other resources that are more beneficial at the time, or that they have been empowered to seek other technologies [43] Papers included in the scoping review are identified with a (*) in the final reference list.…”
Section: Discussionmentioning
confidence: 99%
“…status, privacy and security, adaptation of app use to the user's routine, initial training and ongoing technical support [43]. The self-determination aspect is also important: "They're taking responsibility for their own monitoring of their health as well, you know, we're not just, sending letters out and, and wanting them to come in and do it.…”
Section: Discussionmentioning
confidence: 99%
“…These engagement strategies motivate individuals to adhere to treatment plans, make healthier choices, and actively participate in healthcare. Increased engagement can lead to improved treatment outcomes [ 26 ].…”
Section: Reviewmentioning
confidence: 99%